THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND SELF-HARMING BEHAVIOR AMONG STUDENTS - Putri, Shela Amelia Septiyanti; Widodo, Arif (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Background: Mental health problems among university students are increasing and may lead to maladaptive coping behaviors, including self-harm. Self-harm is defined as intentional self-injury without suicidal intent, commonly used as a means of regulating emotional distress. Family support is considered a key protective factor that can enhance emotional stability and reduce the risk of self-harm behavior. Objective: This study aims to determine the relationship between family support and self-harming behavior in undergraduate nursing students at Muhammadiyah University of Surakarta Method: This research was quantitative with a correlational method. The sample used was 114 students, using a simple random sampling method. Data were collected using a demographic questionnaire, the Family Support Scale (FSS) consisting of 20 items, and the Deliberate Self-Harm Inventory (DSHI) consisting of 16 items. Results: A negative correlation is a relationship between two variables that move in opposite directions, where an increase in one variable is followed by a decrease in the other. In this study, a negative correlation indicates that the higher the family support received by students, the lower the tendency for self-harming behavior, and vice versa. The correlation coefficient value obtained from the Spearman test, r = -0.480, indicates a negative relationship with moderate strength. Conclusion: This can be interpreted as meaning that there is a relationship between family support and self-harming behavior in undergraduate nursing students at Muhammadiyah University of Surakarta.